Gender protest and same-sex desire in antebellum American literature : Margaret Fuller, Edgar Allan Poe, Nathaniel Hawthorne, and Herman Melville /: Margaret Fuller, Edgar Allan Poe, Nathaniel Hawthorne, and Herman Melville. (2016) - Greven, David
No abstract available